Postcolonial Reading of the Bible: (Evangelical) Friend or Foe? - Ferry Y. Mamahit (Sekolah Tinggi Theologia Jaffray, 2021)
Reading the Bible through a postcolonial lens has become today’s trend in biblical hermeneutics. It triggers pros and cons within the evangelical circle. Is it friend or foe? Rather than uncritically accepting or refusing it, the article chooses a middle way, being “open but cautious” toward it. The article assumes that every reading method has its strengths and weaknesses and, thus, it can offer valuable things. Applying the content analysis theory, the author finds that a postcolonial biblical reading is somehow relevant to a contextual and transformative biblical reading, regardless of its multiple problems. It enables the readers to be self-critical, context-sensitive, and practical in faith-life integration. The article concludes that postcolonial reading of the Bible can be both (evangelical) friend and foe.